2013
DOI: 10.1097/tp.0b013e318273878c
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Antibodies to Class II Antigens Are Associated With Accelerated Cardiac Allograft Vasculopathy

Abstract: Background Although a link between donor-specific antibodies against human leukocyte antigens type II (DSA II+) and transplant glomerulopathy has been clearly established, its role in cardiac allograft vasculopathy (CAV) is unclear. Methods DSA were evaluated using solid phase Single Antigen Bead assay before transplant in 51 heart transplant (HTX) recipients. Coronary angiography and three-dimensional intravascular ultrasound (3D IVUS) were performed at baseline and approximately one year after the baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…Toplisky et al analyzed the relation of preformed DSA measured by SAB assay and CAV in heart transplant recipients, and found that the presence of preformed class II DSA were associated with an increased risk for accelerated CAV as detected by 3-dimensional volumetric intravascular ultrasound. (13) Although serial post-transplant DSA levels were not reported in their study, these results taken together with our findings shed further light on the pathologic roles of class I and II DSA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Toplisky et al analyzed the relation of preformed DSA measured by SAB assay and CAV in heart transplant recipients, and found that the presence of preformed class II DSA were associated with an increased risk for accelerated CAV as detected by 3-dimensional volumetric intravascular ultrasound. (13) Although serial post-transplant DSA levels were not reported in their study, these results taken together with our findings shed further light on the pathologic roles of class I and II DSA.…”
Section: Discussionsupporting
confidence: 70%
“…In our laboratory MFI levels <300 are not reported because they are considered beyond the sensitivity of the assay. (13,22)…”
Section: Methodsmentioning
confidence: 99%
“…15,16 However, one exception might be that mismatched class II molecules in the endothelium of graft coronary arteries could predispose recipients to allograft vasculopathy, an association reported in adult recipients of heart transplants 7 and supported by data suggesting that DSAs against class II HLA molecules may be associated with allograft vasculopathy. 17,18 Because of limitations in the SRTR database, we were unable to determine the cause of graft failure or compare the risks of rejection and allograft vasculopathy in our groups. Because cardiac allograft vasculopathy seems to be less common and less aggressive in pediatric recipients, 19 it is possible that its contribution to graft failure via class II HLA mismatching may not have been apparent in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An additional research question is whether treatment of DSA without concomitant pAMR is warranted. DSA have previously been shown to increase cellular rejection (2), CAV (3–5), and mortality (68). The additional findings of this study demonstrating Class II DSA increase the risk of future AMR, increase the risk of graft dysfunction with AMR, and that de-novo Class II DSA increase the risk of graft loss, suggest there is sufficient evidence to prompt a clinical trial for the treatment of Class II DSA in the absence of AMR.…”
Section: Discussionmentioning
confidence: 99%
“…(1) It is known that DSA are detrimental following orthotopic heart transplantation (OHT), leading to increased cellular rejection (2), cardiac allograft vasculopathy (CAV) (3–5), antibody mediated rejection (AMR) (4), and mortality. (68) Prior to 2010, International Society for Heart and Lung Transplantation (ISHLT) guidelines for the diagnosis of AMR required the presence of DSA.…”
Section: Introductionmentioning
confidence: 99%